Millennial Generation Investment Interest through Financial Technology in the Post-Covid-19 Pandemic Period - Anisa Sains Kharisma; Amelia Sholeha (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the effect of financial literacy, personnal interest and enviromental on the interest milenial generation to invest by financial technology. This type of research is quantitative. The population of this study were students of the Accounting Study Program of the Faculty of Economics and Business, Muhadi Setiabudi University with the sample criteria of active student and those who were or had taken capital market and financial management course. Data collection in this study using the questionnaire method. Instrument testing was analyzed using validity test and reliability test. Data analysis techniques used in this study by SmartPLS. The result showed that financial literacy, personnal interest and environment had a positif significant effect on investment interest by financial technology.